2000
DOI: 10.1074/jbc.m007691200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Variants Altered at the N-terminal Proline, a Novel Heme-Axial Ligand in CooA, the CO-sensing Transcriptional Activator

Abstract: CooA, the carbon monoxide-sensing transcription factor from Rhodospirillum rubrum, binds CO through a heme moiety resulting in conformational changes that promote DNA binding. The crystal structure shows that the N-terminal Pro 2 of one subunit (Met 1 is removed post-translationally) provides one ligand to the heme of the other subunit in the CooA homodimer. To determine the importance of this novel ligand and the contiguous residues to CooA function, we have altered the N terminus through two approaches: site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
77
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(89 citation statements)
references
References 40 publications
12
77
0
Order By: Relevance
“…Recently, the x-ray crystal structure of Fe(II) CooA was solved to 2.6-Å resolution and revealed that Pro 2 of one monomer serves as one ligand to the heme iron of the other monomer and that the ligand trans to Pro 2 is His 77 (8). Previous studies, including electron paramagnetic resonance (EPR) 1 analysis and site-directed mutagenesis showed that one of the ligands in the Fe(III) form is Cys 75 in the thiolate form (7,9), and Pro 2 is assumed to be the trans ligand, based on indirect evidence (10,11). Thus, there is an unusual ligand switch upon reduction of the heme, with His 77 replacing Cys 75 (7,12).…”
mentioning
confidence: 99%
“…Recently, the x-ray crystal structure of Fe(II) CooA was solved to 2.6-Å resolution and revealed that Pro 2 of one monomer serves as one ligand to the heme iron of the other monomer and that the ligand trans to Pro 2 is His 77 (8). Previous studies, including electron paramagnetic resonance (EPR) 1 analysis and site-directed mutagenesis showed that one of the ligands in the Fe(III) form is Cys 75 in the thiolate form (7,9), and Pro 2 is assumed to be the trans ligand, based on indirect evidence (10,11). Thus, there is an unusual ligand switch upon reduction of the heme, with His 77 replacing Cys 75 (7,12).…”
mentioning
confidence: 99%
“…Fluorescence Polarization Assay for DNA Binding-In vitro DNA binding of CooA preparations was measured using a fluorescence polarization assay as described (28,29).…”
Section: Methodsmentioning
confidence: 99%
“…Although a comparison of the structure of effectorbound CRP with effector-free CooA shows a significant repositioning of the AR3 region (8) (Fig. 1), (28,30). There is strong reason to believe that CO binding perturbs the position of the heme 6 and, therefore, His 77 , Asn 42 , and Glu 41 residues as well.…”
Section: Isolation Of Gain-of-function Variants Altered At the Surfacmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to examine the specific association of CooA to Azu DNA in a CO-dependent manner, we carried out a gel mobility assay with Azu DNA or pristine ds-oligo-DNA containing CooA binding sequence (27 bp) 16 (Figure 2a). As previously reported, CO CooA caused a distinctive band shift of the pristine ds-oligo-DNA (Lane 3), 21 which was not observed for CooA in the CO-unbound form (Lane 2).…”
mentioning
confidence: 99%